IDENTIFIKASI KEBUTUHAN SISTEM MONITORING DAN PENGENDALIAN MULTI-PROYEK KONSTRUKSI DENGAN METODE HOUSE OF QUALITY Studi Kasus: Dinas Pekerjaan Umum Kabupaten Gresik - Siswanto, Agus; Baihaqi, Imam (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
Every year, the committing officer, then called as PPK, as the manager of the owner construction project in the local government and its team often handles more than 50 (fifty) construction projects termed “multi construction projects”. This study aims to identify the design needs of monitoring and controlling multi-construction projects system in the local government in order to be developed as a reference needs of monitoring and controlling system software. This study began by identifying the needs of PPK and stakeholders through interviews related to the system software that will be developed. The interview results were then grouped and described as “customer requirement attributes” and then made the “importance” level values of those attributes as a questionnaire. The quality result concluded that all customer requirements attributes were considered important with the total score range at 123–171 from the “importance” standard score is 105. Then a functional requirement was made for each customer requirement and analyzed using a method adopted from house of quality (HoQ) with final results are; the highest percentage from 36 (thirty six) of the relative importance weight from functional requirements is 6.42 percent and the lowest is 1.24 percent with 5 (five) highest sequences are 4.78 percent-6.42 percent.